Adapting and deploying a digital program for training non-specialist providers on a brief psychological intervention for depression in rural Gujarat, India. - Aakrushi Brahmbhatt; Darshana Rathod; Udita Joshi; Azaz Khan; G Sai Teja; Shrey Desai; Ajay Chauhan; Shobha Shah; Deepti Bhatt; Sethuraman Venkatraman; Deepak Tugnawat; Satchit Balsari; et al. (PLOS Global Public Health)
Workforce shortages represent a major bottleneck to delivering depression care, particularly in lower resource settings. This pilot study aimed to assess the acceptability and feasibility of a digital training program on developing knowledge and skills in the delivery of a brief behavioral activation intervention for depression among non-specialist providers (NSPs) in Gujarat, India. Participating NSPs, such as community health workers and other frontline providers without specialized training in mental health care, were provided access to a digital program covering the core skills and content necessary to deliver the Healthy Activity Program, an evidence-based behavioral activation intervention for depression. NSPs completed knowledge assessments before and after the digital training, followed by focus group discussions to gather their feedback about the program content and delivery format. Of 43 NSPs enrolled in this study, 67% (n = 29) were community health workers called Accredited Social Health Activists and 33% (n = 14) were frontline mid-level health providers called Community Health Officers. Most participants (n = 39; 91%) completed the full course. Knowledge assessment scores showed improvement from pre-training (mean = 29.96; 95% CI: 27.12-32.81) to post-training (mean = 34.62; 95% CI: 31.05-38.19; p = 0.0448). Focus group discussions revealed that participants appreciated the digital mode of training despite facing technical challenges while completing the course. This study further supports the feasibility and acceptability of digital approaches for training frontline providers to deliver brief psychological interventions for depression. With adequate resources and proper execution, digital training holds potential to serve as a key tool to build capacity of NSPs and expand the mental health workforce in India.